Fenomena Marriage Is Scary di Era Gen Z: Analisis Tafsir Maqāṣidī Atas Q.S. Rūm Ayat 21 - Eira Kishi Febila Saragih; Salahuddin Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The marriage is scary phenomenon has emerged as a widespread discursive trend among Generation Z through digital platforms such as TikTok, reflecting their growing anxiety and fear toward the institution of marriage. This study aims to analyze the roots of this anxiety and formulate a constructive reconstruction of the Islamic concept of marriage through a maqāṣidī interpretation of Qur’an Surah Ar-Rūm [30]: 21. This research employed a qualitative library research approach by synthesizing the thoughts of Al-Shatibi, M. Quraish Shihab, and Ibn ‘Ashur. The findings reveal that Generation Z’s anxiety is driven by the imbalance between the ideal teachings of Islam and the realities of domestic conflict widely portrayed on social media. The maqāṣidī perspective emphasizes that marriage is a divinely prescribed mechanism to achieve dynamic tranquility (sakinah) through the pillars of love (mawaddah) and compassion (rahmah), serving as instruments for the protection of life (ḥifẓ al-nafs) and the preservation of lineage (ḥifẓ al-nasl). The novelty of this study lies in transforming the interpretation of Qur’an Surah Ar-Rūm [30]: 21 into a theological-psychological methodological framework that is responsive in countering the marriage is scary narrative within the contemporary digital culture.